2018
DOI: 10.1016/j.jad.2018.04.057
|View full text |Cite
|
Sign up to set email alerts
|

‘Cool’ and ‘Hot’ executive functions in suicide attempters with major depressive disorder

Abstract: The disrupted 'cool' EFs patients with MDD are consistent with previous review and meta-analytic studies. On the other hand, the two groups with MDD performed similarly to the healthy controls in the 'hot' EF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 48 publications
2
13
1
Order By: Relevance
“…Only the depressed patients with suicidal ideation showed executive dysfunctions, particularly in the decision-making tasks. In a more recent study by Ming-Chou Ho et al [37] where they evaluated the EF of 34 MDD attempters, 36 MDD non-attempters, and 55 healthy controls their findings were consistent with previous review and meta-analytic studies. To date there is no longitudinal study following first depressive episodes, which examine whether alterations in one or more EF, or other cognitive alterations, will predict suicidal ideation, attempts or subsequent consummate suicidal behavior.…”
Section: Introductionsupporting
confidence: 82%
“…Only the depressed patients with suicidal ideation showed executive dysfunctions, particularly in the decision-making tasks. In a more recent study by Ming-Chou Ho et al [37] where they evaluated the EF of 34 MDD attempters, 36 MDD non-attempters, and 55 healthy controls their findings were consistent with previous review and meta-analytic studies. To date there is no longitudinal study following first depressive episodes, which examine whether alterations in one or more EF, or other cognitive alterations, will predict suicidal ideation, attempts or subsequent consummate suicidal behavior.…”
Section: Introductionsupporting
confidence: 82%
“…133,136 One of the neuropsychological domains strongly impaired in MDD regards the executive function, a set of self-regulatory cognitive processes essential for adaptive behaviour. [137][138][139][140][141][142][143]…”
Section: Neuropsychological and Neurocognitive Factorsmentioning
confidence: 99%
“…Some studies found that patients with MDD exhibited lower net scores on IGT compared with HCs (Cella et al, ; Moniz et al, ; Must et al, ), while Smoski et al () reported an opposite result with a better performance of IGT in the MDD group. There are also some researchers reporting no significant difference in net scores of IGT between patients with MDD and HCs (Deisenhammer, Schmid, Kemmler, Moser, & Delazer, ; Ho, Hsu, Lu, Gossop, & Chen, ; Saperia et al, ). In patients with BD, the results are also complicated.…”
mentioning
confidence: 99%